Organizational and Workplace Related Factors Influencing Transfer of Learning (Socio-Economic Development Panorama, 2009)
Training literature and previous studies on transfer of training provide evidences to support the claim that training works when it is theoretically driven, focused on required competencies, designed to provide trainees with realistic opportunities to practice, and to give and receive feedback. However, some important questions about the transfer of training have not yet been critically examined to explain success or failure of training as intervention strategies used for human resource development. Some of these questions are, for example: What are the critical factors that facilitate or inhibit the process of transfer of knowledge, skills and attitudes from training to workplace? Which of those factors in the organizational environment can be manipulated to maximize transfer? What are the supervisory behaviors or patterns of behavior that can facilitate generalization and maintenance of knowledge and skills from a training context to the work-environment? What could be the roles of different actors in the organizational set up and workplace contexts so as to facilitate positive transfer of learning from training to job?This article presents a brief review of related literature and previous research on organizational and workplace related factors that influence transfer of learning from the training to workplace contexts. In addition to the design and delivery, the extent of transfer of training interventions largely depend upon the culture of the organization and contexts of workplaces where employees are expected to apply the knowledge, skills, and attitudes they have gained through training and development interventions. This review captures some of the critical aspects of transfer of training that include the influence of workplace and supervisory roles that in fact need further research.Key words: Training; transfer of knowledge; post training supervision; workplace; human resource developmentSocio Economic Development Panorama; Vol. 1; No. 4, 2009; January-June